The Reach and Community Perspective of BT Radio Programs as Supplemental Teaching and Learning Platforms - Mangubat, Fernando N, Jr; Bajao, Naomi A; Sarucam, Jae-an V; Gabuya, Alden Q, Jr.; Mangubat, Florieza M (UI Scholars Hub, 2024)
In 2020, COVID-19 forced several communities to isolate, and radio stations stepped up as leaders in communication and media during the pandemic, especially in rural communities where internet access is lacking. This study examines the vital role for disseminating information among urban and rural communities and improving services for clients who do not have access to the internet or television news updates. Specifically, this study analyses the demographics of the listeners of Bulawanong Tinubdan (BT) Radio 98.1 FM, a radio station of the Cebu Technological University-Tuburan campus and an affiliate of the Philippine Broadcasting Service (PBS), a government-owned network. It delves into the community perspective of the station’s programs, as BT Radio 98.1 FM endeavors to be an avenue for communication as well as teaching-learning platform during unexpected lifestyle changes like the COVID-19 pandemic. In addition, this study seeks to ascertain how listeners perceive the role of BT Radio programs in assisting the community in becoming more connected despite these constraints. The results show that the station captures the majority of the younger audiences in the community, while also highlighting how a campus-based FM radio station promotes community awareness across different age groups. This strengthens the position of the radio program as a learning environment that is widely accessible and that promotes information in the community.